In the name of the mermaid princess. 1 - Fumikawa, Yoshino; Garrity, Shaenon K. (Shojo beat manga., 2024)
In a society hostile to diversity, can mermaid princess Mio be true to herself? In the classic fairy tale, a mermaid princess gives up her special abilities for love. What happens if she doesn't? Princess Mio is betrothed to Prince Chika. However, they've never met, and he doesn't know her secret--she's a mermaid! When her tutor, Yuri, takes her out of the castle to meet her subjects, Mio begins to accept her true self. But Yuri has a secret too... And when Mio tells her father, the king, she wants to live life openly as a mermaid, he punishes her. How can she stay true to herself?